Characterization of methylglyoxal-modified human IgG by physicochemical methods. Issue 12 (10th September 2018) - Khan, Mohd. Adnan; Arif, Zarina; Moinuddin,; Alam, Khursheed
Abstract : Human IgG is a defence protein and quite reactive to dicarbonyls. In this study, methylglyoxal-induced modification of IgG was examined by various biochemical and biophysical methods. The methylglyoxal-induced changes in IgG were monitored by UV-visible and fluorescence spectroscopy, Fourier transform infrared spectroscopy, 1-anilinonaphthalene-8-sulfonic acid (ANS), and thermal denaturation studies. Aggregate formation was studied by Thioflavin T (ThT), Congo red (CR) and scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Spectroscopic studies suggested gross changes in MGO-modified IgG. Fluorogenic AGEs appeared during modification and the MGO-modified IgG gained thermostability. The reaction produced oxidative stress in the medium because carbonyl content increased manifold and sulfhydryl groups decreased. Enhanced binding of the MGO-modified IgG by Congo red and Thioflavin T suggests crosslinking and aggregation. This was supported by SEM and TEM results. Abstract :